Judicial reforms - Need of the hour - Narayan, Jayaprakash (1999)
Taking a look at the serious inadequacies of our judicial system and the grave consequences of its impending failure, the author presents his package of reforms. This includes creation of: (1) rural courts, (2) Indian Judicial Service, (3) Judicial Commission on Judges' Accountability, and (4) an independent crime investigation force; besides pruning appellate jurisdiction of High Courts. - Reproduced
Keywords: Judiciary - India; Judiciary